Decolonising the Hajj: the pilgrimage from Nigeria to Mecca under empire and independence - Heaton, Matthew M. (Studies in imperialism, 2023)
This book recounts the effects of British colonial rule and decolonization on the transformation of the pilgrimage to Mecca (Hajj) from Nigeria over the course of the twentieth century. In so doing, it incorporates Nigeria into broader historical understanding of one of the most important transnational processes in the world